2000
DOI: 10.1096/fj.00-0144com
|View full text |Cite
|
Sign up to set email alerts
|

Human respiratory syncytial virus vaccine antigen produced in plants

Abstract: Human respiratory syncytial virus (RSV) is the primary cause of respiratory infection in infants worldwide. Currently there is no available vaccine, although studies in animal models have demonstrated protective immunity induced by an epitope of the RSV G-protein representing amino acids 174-187. Two peptides containing amino acids 174-187 of the G-protein of the human RSV A2 strain (NF1-RSV/172-187 and NF2-RSV/170-191) were separately engineered as translational fusions with the alfalfa mosaic virus coat prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 37 publications
(32 reference statements)
0
19
0
2
Order By: Relevance
“…There was also development of another vaccine which followed the first one by expression of hepatitis B surface antigens in plants [57]. Now there are many different types of proteins which are successfully expressed in plants, such as E. coli heatlabile enterotoxin antigen [58], granulocyte macrophage colony stimulating factor [59], human serum albumin [60], enkephalins [61] and glucocerebrosidase, surface antigen of Norwalk virus [53], VP1 antigen from foot and mouth disease virus [62,63], B subunit of cholera toxin [54], antigen of rabies virus [51], transmissible gastroenteritis coronavirus's S protein [64,65], G and F proteins of respiratory syncytial virus [66], rotaviral VP6 protein [67], rinderpest [68], and the measles [69] from the major surface antigen of Plasmodium falciparum (an epitope) [70] and virus hemagglutinin proteins. Some plant based vaccines under clinical trials are given in Table 2.…”
Section: Historymentioning
confidence: 99%
“…There was also development of another vaccine which followed the first one by expression of hepatitis B surface antigens in plants [57]. Now there are many different types of proteins which are successfully expressed in plants, such as E. coli heatlabile enterotoxin antigen [58], granulocyte macrophage colony stimulating factor [59], human serum albumin [60], enkephalins [61] and glucocerebrosidase, surface antigen of Norwalk virus [53], VP1 antigen from foot and mouth disease virus [62,63], B subunit of cholera toxin [54], antigen of rabies virus [51], transmissible gastroenteritis coronavirus's S protein [64,65], G and F proteins of respiratory syncytial virus [66], rotaviral VP6 protein [67], rinderpest [68], and the measles [69] from the major surface antigen of Plasmodium falciparum (an epitope) [70] and virus hemagglutinin proteins. Some plant based vaccines under clinical trials are given in Table 2.…”
Section: Historymentioning
confidence: 99%
“…Since then, several proteins of different origin have been expressed in plants. These include Escherichia coli heat-labile enterotoxin antigen [11], Enkephalins [12], Human serum albumin [13], Glucocerebrosidase and granulocyte macrophage colony stimulating factor [14], Norwalk virus surface protein [15], VP1 antigen from foot and mouth disease virus [16,17], cholera toxin B subunit [18], Rabies antigen [19], the S protein of transmissible gastroenteritis coronavirus [20,21], Respiratory synctial virus G and F proteins [8,22], the VP6 protein of rotavirus [23], the measles [24] and Rinderpest [25], virus hemagglutinin proteins and an epitope from the major surface antigen of Plasmodium falciparum [26].…”
Section: General Consideration Of Plant Vaccines Historymentioning
confidence: 99%
“…Sequences from the human rhinovirus (HRV) and HIV-1 coat proteins were fused onto the CPMV small coat protein and inoculated into rabbits with a subsequent immunogenic response (Porta et al, 1994). Additional examples of CVP vaccines derived from a variety of plant viruses include epitopes from human respiratory syncytial virus (RSV) G-protein (Belanger et al, 2000), human rabies glycoprotein (Yusibov et al, 1997;Modelska et al, 1998). Staphylococcus aureus fibronectin-binding protein (Rennermalm et al, 2001), HIV (McLain et al, 1995Durrani et al, 1998;Marusic et al, 2001) and circumsporozoite protein from the malarial parasite (Turpen et al, 1995) have been fused to various CVP structures and have been shown to elicit specific Downloaded by [The University of Manchester Library] at 02:12 12 October 2014 antibody responses in mice.…”
Section: Virus Coat Protein Fusions As Vaccinesmentioning
confidence: 99%